Potensi Serbuk Kayu Puspa Sebagai Pembuatan Papan Partikel Untuk Pengaplikasian Produk Furniture - Novizal, Novizal; Yuliyanto, Yuliyanto; Rollastin, Boy (Jurnal Inovasi Teknologi Terapan, 2025)
In order to meet the needs and desires of human life, science and technology have experienced rapid progress. Science and technology have developed in various aspects of life. Technological progress has also occurred in composite materials which are still being researched. Particle board is an artificial board made by pressing industrial waste from plantations, forestry, and agriculture together with organic adhesives. Low-quality wood waste products that may contain cellulose and lignin, such as sawdust, twigs, turning residues, and others, can be utilized. In this study, which was carried out using the direct experimental method. The parameters used were mesh 10, 20, and 30 with volume fractions of 60%: 40%, 70%: 30%, and 80%: 20%. In this study, the results of the largest impact strength were found in the volume fraction of 60%:40% on mesh 30 with a result of 16.34 J/m2 and the smallest impact value was found in the volume fraction of 70%:30% on mesh 10 of 9.28 J/m2 where this value does not meet the SNI-03-2105-2006 standard for making particle boards.